If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) + 48 = -4x Reorder the terms: 4(2 + x) + 48 = -4x (2 * 4 + x * 4) + 48 = -4x (8 + 4x) + 48 = -4x Reorder the terms: 8 + 48 + 4x = -4x Combine like terms: 8 + 48 = 56 56 + 4x = -4x Solving 56 + 4x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 56 + 4x + 4x = -4x + 4x Combine like terms: 4x + 4x = 8x 56 + 8x = -4x + 4x Combine like terms: -4x + 4x = 0 56 + 8x = 0 Add '-56' to each side of the equation. 56 + -56 + 8x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + 8x = 0 + -56 8x = 0 + -56 Combine like terms: 0 + -56 = -56 8x = -56 Divide each side by '8'. x = -7 Simplifying x = -7
| 10x+5=11x-5 | | 5(-3)(4-7)+9=49 | | 2x+11=-9x-8x | | 9x+2=5x+18 | | h+b+h+b= | | 9(x+5)+3(x+5)=5x-5 | | 6+4x-2=9x+4-4r | | -25+5x=50 | | 3/10-3/56 | | 3(-4)=-12 | | 1/6(4x+70)=3x | | 2x+36=48 | | 10(t-5)+4t=7(t+5)-9 | | 2y+84=106 | | 6+(-7/4) | | 5(x-6y)= | | -7x+x-7-4x+3=6(X-2)x+19 | | 3.25n=-39 | | 3.25=-39 | | (25/36)=x | | 3=-1-j | | -26+n=39 | | 1/4*-7 | | p+1=-1 | | n/3.25=4 | | (4-2y)/2 | | 2(x+5)=4x-1 | | 1=-2-j | | j-2=4 | | 5x^2+48x+36/10x^2+48x | | x^3+6x^2= | | 27.4=p-28 |